Carboxypeptidase U (TAFIa): a metallocarboxypeptidase with a distinct role in haemostasis and a possible risk factor for thrombotic disease - Leurs, Judith; Hendriks, Dirk (Thrombosis and haemostasis, 2005)
Since the discovery of Carboxypeptidase U (CPU) in 1988, considerable information has been gathered about its biochemistry and function in physiological and pathophysiological circumstances. A variety of tools such as assays to measure proCPU and CPU, antibodies raised against (pro)CPU, selective CPU inhibitors and knock-out mice have been developed and are currently being used to explore the role of this metallocarboxypeptidase in different in vivo and in vitro settings. The knowledge that proCPU can be activated by thrombin and plasmin, enzymes with a key function in coagulation and fibrinolysis, and the ability of CPU to remove C-terminal lysine residues has led to the hypothesis that the proCPU/CPU pathway plays a role in the balance between coagulation and fibrinolysis. The maintenance of the equilibrium between coagulation and fibrinolysis is crucial for normal haemostasis and disturbance of this delicate balance can lead either to bleeding tendency or thrombosis. This review provides an update on several aspects of CPU known at the moment, including an extensive overview on the clinical studies performed up till now.